Medium Perfusion Flow Improves Osteogenic Commitment of Human Stromal Cells. (2nd May 2019) - Pasini, Alice; Lovecchio, Joseph; Ferretti, Giulia; Giordano, Emanuele
Abstract : Dynamic culture protocols have recently emerged as part of (bone) tissue engineering strategies due to their ability to represent a more physiological cell environment in vitro. Here, we described how a perfusion flow induced by a simple bioreactor system improves proliferation and osteogenic commitment of human bone marrow stromal cells. L88/5 cells were cultured in poly(methyl methacrylate) custom-milled communicating well plates, in the presence of an osteogenic cocktail containing 1 α, 25-dihydroxyvitamin D3, L-ascorbic acid 2-phosphate, and β -glycerophosphate. The dynamic cell culture was maintained under perfusion flow stimulation at 1 mL/min for up to 4 days and compared with a static control condition. A cell viability assay showed that the proliferation associated with the dynamic cell culture was 20% higher vs. the static condition. A significantly higher upregulation of the osteogenic markers runt-related transcription factor 2 (RUNX2), collagen type I (COL1A1), osteocalcin (BGLAP), alkaline phosphatase (ALPL), and osteopontin (SPP1) was detected when the perfusion flow stimulation was administered to the cells treated with the osteogenic cocktail. An in silico analysis showed that in the dynamic cell culture condition (i) the shear stress in the proximity of the cell layer approximates 10 -3 Pa, (ii) the nutrient and the waste product concentration is more homogeneously distributed than in the static counterpart, and (iii) perfusion flow was associated with higher nutrient consumption. In summary, increased cell proliferation and enhanced early phenotype commitment indicate that dynamic cell culture conditions, delivered via bioreactor systems, produce an enhanced in vitro environment for both basic and translational research in tissue engineering and regenerative medicine.